A saúde emocional do educador: saberes necessários aos trabalhadores da educação - Pereira, Valéria Resende Teixeira (2005)
The present research was conducted in the Masters Degree in Education Program of the Universidade Federal de Uberlândia, betweem February 2003 and February 2005, on educators emotional health. Two previous researches were essential to the start of the present, one conducted by Codo (2002) and the second conducted by Mota (1999). Codo s research studied Brazilian educators work conditions and mental health; it s a thorough and extensive research investigation on the educators burnout syndrome. In Mota s research, entitled Princípios reichianos fundamentais para a educação: base para a formação do professor essential reichian principles for education: foundation for teachers education, the author proposes that we consider in teacher education the conception on an energetic man recognized by Wilhelm Reich. Concerned with educators emotional state, who have complained of not feeling well in their profession, we have tried to understand their suffering. In this study, we focus on the theory developed by Reich, founder of the corporal psychotherapy, which brings us knowledge on emotional health. We tried to understand educators emotional pains, by focusing on the need to seek awareness of their own corporality. Starting with lectures on the burnout syndrome and corporal dynamics, when we were in contact with approximately 60 educators from city educational institutions, selecting the nine people who become the subjects of this study. We were researching for educators with the burnout syndrome. However, we have come to the conclusion that our subjects do not have such disease, because, in our understanding, they work with alphabetization, a learning phase filled with affective relations. Alphabetization is an emotional process, where a lot of affection is exchanged between the ones involved. Also considering that the burnout syndrome sets in the educators body when the affectionate relation with the student is not established, and the work environment is reason for anguish, the educators interviewed were involved in their work, and the affective bond was being established with the students. Our subjects could count on the support and recognition from their colleagues and coordination. Therefore, they were not exposed to the favorable conditions for developing this disease. From this paper we can conclude that investing in educators emotional health is an strategic and necessary action in times like this, and it ll allow for educators themselves to find ways to cope with their day to day problems. Corporality in the educational process once looked at from the phenomenology and corporal psychotherapy perspective, can become a wide field of possibilities to rescue man and creativity, sensibility and identity within oneself, and his own social-historical and cultural environment.